Control of immune-mediated disease of the central nervous system with monoclonal (CD4-specific) antibodies. - O'Neill, J; Baker, D; Davison, A; Allen, S; Butter, C; Waldmann, H; Turk, J (1993)
Chronic relapsing experimental allergic encephalomyelitis (CREAE) was induced in Biozzi AB/H (H-2dq1) mice by active sensitization with spinal cord antigens. A single i.p. injection of CD8-depleting (YTS169.4) monoclonal antibody (mAb) failed to affect the clinical course of CREAE when administered prior to and during the onset of both the initial clinical and subsequent relapse phase of the disease. By contrast similar treatment with both CD4-depleting (YTS191.1) or CD4-blocking/non-depleting (YTS177.9) mAb significantly inhibited disease progression. Treatment shortly before the anticipated onset of clinical EAE prevented the subsequent development of disease, although disease could be provoked following antigen-rechallenge. In contrast, treatment with these antibodies during post-acute remission phase mainly served to delay the incidence of relapse. This suggests that, unless tolerance can be re-induced, treatment of ongoing neuroimmunological disease will require 'pulse' therapy and thus potentiate the problems of long-term immunosuppresion. Despite the findings that CD4-specific antibodies can rapidly reverse overt clinical disease shortly after the onset of disease exacerbation, once neurological dysfunction becomes established anti-CD4 treatment fails to improve the animals clinically, possibly due to the inability to rapidly reverse established demyelination. Although this study does not exclude the potential central action of the injected mAb, the failure to significantly dissociate therapeutic benefit between mAb administered directly into the CNS and that given systemically suggests that a major action of these agents is probably by selectively removing T cells in the peripheral T cell pool.